KUMARIN TERISOPRENILASI DAN ALKALOID INDOL DARI KULIT BATANG Zanthoxylum ovalifolium TUTCHER - Mulyadi Tanjung (JURNAL KIMIA MULAWARMAN, 2018)
Two isoprenylated coumarins, imperatorin (1), isopimpinelin (2) and one indol alkaloid compound, canthine-6-one (3) were isolated from the stem bark of Zanthoxylum ovalifolium Tutcher. Their structures were determined based on spectroscopic data such as UV, IR, MS and NMR. Imperatorin (1) showed high activity toward DPPH radical and isopimpinelin (2) and chantine-6-one (3) has moderate activity.